2(0.3x+4)-1=1.33x-3+x

Simple and best practice solution for 2(0.3x+4)-1=1.33x-3+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(0.3x+4)-1=1.33x-3+x equation:


2(0.3x+4)-1=1.33x-3+x

We simplify the equation to the form, which is simple to understand
2(0.3x+4)-1=1.33x-3+x

Reorder the terms in parentheses
+( + 0.6x+8)-1=1.33x-3+x

Remove unnecessary parentheses
+ 0.6x+8-1=+1.33x-3+x

We move all terms containing x to the left and all other terms to the right.
+ 0.6x-1.33x-1x=-3-8+1

We simplify left and right side of the equation.
-1.73x=-10

We divide both sides of the equation by -1.73 to get x.
x=5.78034682081

See similar equations:

| 25+(5x)=50+(10x) | | 10pq+8p= | | -3h-4=h-8 | | 4=(m+13) | | 81-x=93-2x | | 5+-11t=7(5+-2t) | | 8x^2+7x-4=0 | | 7g(-3h+1)= | | 81-x=93-x | | 2a+2=a+4 | | 79-(101-5y)=2(101-5y)+y | | 6.5(x-4)=-0.5x+30 | | 5=(x+8) | | -5x+6y=30 | | 19x=12x | | 11x+2=5x+10+58 | | -5-x=1+2x | | 4d=7-7 | | 8x+2+70+60= | | -5(a-6)+2a=9 | | (3x-6y-1)+(-x+y+10)= | | 3w+10=-3+8w-9w | | 4(2y+1)-2y=-26 | | 1/3(102-12c)=5(3c+10) | | 5x-x-3=2x+6 | | M-3=7m-21 | | 4n-(7-6n)=13 | | 6x+3=3(2x+3) | | 2x-11=23 | | 3x=52 | | (9x-8y-11)-(5x-9y+1)= | | -8=1.3x+x |

Equations solver categories